(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Provision of adequate drinking water for villagers is an inseparable part of the government’s efforts to meet one of the basic human needs. The inherent and fundamental water needs are increasing along with the increase in population, moderation of life and the level of economic progress of the Pamsimas community is one of the mainstay programs of the government in the provision of clean water and sanitation for rural and suburban communities through community-based approaches. The Pamsimas program began in 2008, where the implementation has so far succeeded in increasing rural and suburban areas that can access drinking water and sanitation services. The program also enhances the value and behavior of clean and healthy living in the population of) the effectiveness of a measure that states how far targets (quantity, quality and time) have been achieved, or the significance of the percentage of targets achieved, the higher the effectiveness. Accuracy of program objectives, program socialization and program monitoring In this study, researchers used a type of descriptive study using a qualitative approach. This research approach was chosen because the researcher wanted to solve the problem by describing or describing the current state of the object of the researcher based on the facts that exist and described in the form of words and language obtained from observations, interviews and documents. Monitoring is the process of supervision or checking program activities is it appropriate that is wasted and in the pamsimas program is very wasted the monitoring process from the village government as a service program supervisor in order to be able to carry out the monitoring process pamsimas program includes actions Program Objectives Not exactly needed water debit cannot meet the needs of the community so that the community in the provision of water services The program has been carried out to the community by the village government in the form of socialization within the community. Program Monitoring has been carried out by the village government through supervision and coordination between the government and PAMSIMAS management The target of the PAMSIMAS program must be expanded in accordance with the needs of the community. Socialization of the PAMSIMAS program is still being carried out to the community. There is a need for supervision from the community regarding PAMSIMAS management. Keywords: Stipulation, Program, Monitoring, Socialization Target.